Mega-disruptions and policy change: Lessons from the mobility sector in response to the Covid-19 pandemic in the UK. (September 2021) - Marsden, Greg; Docherty, Iain
Abstract: There has been widespread interest in the potential for the significant behavioural and policy adaptations rendered necessary by Coronavirus to act as a catalyst for radical longer term policy change in transport. However, this body of work to date has been limited in its consideration of how such policy change might be brought about. Translating the lessons from the Coronavirus response to other ongoing strategic challenges such as decarbonisation requires analysis of what the pandemic has revealed about processes of policy formulation and how institutions responsible for policy implementation actually work. This paper explores the extent to which rapid policy change has actually been possible in the transport sector in England and Scotland during the pandemic, and key examples of how such change has been both achieved and blocked. Two rounds of interviews with senior stakeholders from across the transport sector were undertaken in June and November 2020 to inform the analysis. We find that the pandemic has accelerated some policy commitments that were already planned, but at a time of huge stress on the whole of government and its partner delivery organisations, the potential to deliver radical policy adaptation was limited. However, Coronavirus is recognised as being a potentially path-changing disruption to existing trajectories in terms of the adaptations to business practices, industry structures, ways of working and the public finances. Paradoxically, whilst recognising these uncertainties, decision-makers are yet to deviate from pre-pandemic planning assumptions and policy plans and this risks missing the opportunities to steer how those changes unfold. Highlights: Addresses research gap in the study of governance responses during disruptions. Identifies transport as a distant policy sub-sector in a crisis that affected all parts of government. Finds that the response to the pandemic has accelerated already planned policies but generated few new policies. Long-term impacts on the future structure of cities, use of public transport and uptake of active travel could still emerge. The leading strategic thinkers on transport policy are still unsure what kinds of future demand to plan for.